A comparative study on spin-to-charge and charge-to-spin conversion using modulated Dirac surface states of Bi2Se3 - Youngmin Lee; Jonghoon Kim; Seungwon Rho; Seok-Bo Hong; Hyeongmun Kim; Jaehan Park; Dajung Kim; Chul Kang; Myung-Ho Bae; Mann-Ho Cho (Applied Surface Science Advances)
Understanding the mechanisms of spin-charge interconversion is a major challenge in modern spintronics. In this study, we investigate the complex charge-to-spin conversion (CSC) and spin-to-charge conversion (SCC) using the modulated Dirac surface state of Bi2Se3 thin films. The role of Bi2Se3, which possesses a spin-momentum locked Dirac surface state (DSS), in the CSC and SCC processes is explored using spin-torque ferromagnetic resonance (ST-FMR) and terahertz emission methods, respectively. Distinct differences in spin Hall angles are observed in ultrathin Bi2Se3 films on HfO2-x, compared to those on a typical substrate, indicating the dependence on the spin-orbit interaction. Specifically, the interaction of d-orbital of the unbound hafnium in HfO2-x and Bi2Se3 enhances the spin-orbit interaction. In addition, we found that the complex interaction between the surface and bulk states affects the spin diffusion length and the spin current injection region. The influence of the surface state on the conversion processes decreases as the Bi2Se3 film thickness increases, resulting in differing efficiency for SCC and CSC due to the asymmetrical stack structure. The findings using Bi2Se3 ultrathin films enhance our understanding of DSS-related CSC and SCC mechanisms, paving the way for performance optimization of future spintronic devices.